Strength properties and microstructural characterization of metakaolin geopolymer concrete synthsized at ambient temperature. - Salihu, C. H.; Abalaka, A. E.; Lafiya-Araga, R. A.; Olawuyi, B. J.; Kariim, I. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
Geopolymer concrete has been gaining extensive attention in recent years due to its numerous advantages over Ordinary Portland cement concrete in terms of reduced carbon footprint, improved mechanical strength, durability as well as chemical resistance. However, production of geopolymer concrete is usually affected by several factors such as the synthesis temperature, nature of the source material and the type of alkaline activator used. For these materials to have wider application within the Nigerian construction industry, there is a need to synthesize the concrete at ambient temperature and to examine the suitability of native Alkaleri kaolin to produce geopolymer concrete. The study presents the strength and microstructural properties of Metakaolin Geopolymer Concrete synthesized at ambient temperature. Alkaleri calcined kaolin from Bauchi state Nigeria was used as the main geopolymer precursor with sodium hydroxide and sodium silicate as the alkaline activating agent. The Geopolymer concrete was prepared with Silicon/Aluminium ratio of 2.0 and 2.5 (Geopolymer concrete M1 and M2 respectively) and cured for 3, 7, 14, 28, and 90 days at ambient condition (average temperature of 26°C and average relative humidity of 61± 15%). Fourier Transform Infra-Red, X-ray Diffraction, Thermo-Gravimetric Analysis, Scanning Electron Microscopy as well as compressive strength and split tensile strength test were conducted on the Geopolymer concrete at appropriate curing age to examine their microstructure and strength properties. The Fourier Transform Infra-Red revealed that there was an immediate geopolymeric reaction between the metakaolin and the alkali activator. The X-ray Diffraction showed that the raw metakaolin sample and both Geopolymer concrete M1 and M2 were amorphous in nature; while the Geopolymer concrete M2 (Silicon/Aluminium ratio of 2.5) exhibited good dissolution of the kaolinite which resulted in a more compact and stable structure in comparison with Geopolymer concrete M1 (Silicon/Aluminium ratio of 2.0). This was also confirmed by the Scanning Electron Microscopic images of the Geopolymer concretes. The Thermo-Gravimetric Analysis revealed that both Geopolymer concrete M1 and M2 were thermally stable at 300°C and at 800°C, only the organic phase of the geopolymer decomposed. The strength properties (compressive and tensile strength) of Geopolymer concrete M1 and M2 increased with increase in the curing age, and Geopolymer concrete M2 displayed slightly higher strength in all the curing ages as compared with the Geopolymer concrete M1. This implies that the higher the Silicon/Aluminium ratio, the higher the mechanical strength of the geopolymer. Both the Geopolymer concrete samples attained a compressive strength that can be acceptable for structural use as normal strength concrete grade C20/25 as specified in the requirement of BS EN 206-1 2000 at 28 days curing.